2015
DOI: 10.1080/02755947.2015.1069427
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electronarcosis and Carbon Dioxide Sedation Effects on Travel Time in Adult Chinook and Coho Salmon

Abstract: The immobilization of fish during handling is crucial in avoiding injury to fish and is thought to reduce handling stress. Chemical sedatives have been a primary choice for fish immobilization. However, most chemical sedatives accumulate in tissues, and often food fishes must be held until accumulations degrade to levels safe for human consumption. Historically, there have been few options for nonchemical sedation. Carbon dioxide (CO2) has been widely used for decades as a sedative, and while it does not requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Previous studies on recovery in Chinook Salmon O. tshawytscha indicated that nearly all cardiovascular variables (including heart rate and cardiac output) returned to baseline levels within 5 min of recovery (Hill and Forster 2004), which is consistent with the lack of behavioral differences observed in Largemouth Bass. Similar trends have been reported for postsedation recovery of Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus (Balazik 2015) and Coho Salmon O. kisutch (Keep et al 2015). Although electrosedated fish appeared to be behaviorally affected beyond 5 min postsedation, it is unclear whether increasing the holding time would be the correct solution given that (1) increased activity was the only behavioral difference detected and (2) handling and holding periods can also be stressful.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies on recovery in Chinook Salmon O. tshawytscha indicated that nearly all cardiovascular variables (including heart rate and cardiac output) returned to baseline levels within 5 min of recovery (Hill and Forster 2004), which is consistent with the lack of behavioral differences observed in Largemouth Bass. Similar trends have been reported for postsedation recovery of Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus (Balazik 2015) and Coho Salmon O. kisutch (Keep et al 2015). Although electrosedated fish appeared to be behaviorally affected beyond 5 min postsedation, it is unclear whether increasing the holding time would be the correct solution given that (1) increased activity was the only behavioral difference detected and (2) handling and holding periods can also be stressful.…”
Section: Discussionsupporting
confidence: 69%
“…Electro‐immobilization, which has been described in several species of warmwater and coolwater fishes, including salmonids (Roth et al 2003; Hudson et al 2011), has been found to produce shorter induction and recovery times compared to immersion anesthetics (Keep et al 2015; Johnson et al 2016). Electro‐immobilization has been used for surgical implantation of transmitters in Lake Trout Salvelinus namaycush with no apparent lethal or sublethal effects (Faust et al 2017).…”
mentioning
confidence: 99%
“…In contrast to chemical sedatives (e.g., MS‐222), electrosedation has been found to produce the quickest induction times and recovery times (Keep et al. ; Johnson et al. ) and to reduce handling stress in comparison with chemical sedatives, and the fish may be released immediately posttreatment (Bowzer et al.…”
mentioning
confidence: 99%
“…As an alternative to chemical anesthetics, electrosedation presents benefits in field settings where low contamination, quick recovery times, and immediate release options are advantageous. In contrast to chemical sedatives (e.g., , electrosedation has been found to produce the quickest induction times and recovery times (Keep et al 2015;Johnson et al 2016) and to reduce handling stress in comparison with chemical sedatives, and the fish may be released immediately posttreatment (Bowzer et al 2012;Trushenski et al 2012b). Advancements in electrosedation technology have provided fisheries scientists with various commercially available systems.…”
mentioning
confidence: 99%